2019
DOI: 10.4197/met.28-1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Antimony Leaching from Polyethylene Terephthalate (PETE) into Bottled Water

Abstract: In this research, the level of the heavy metal antimony (Sb) was assessed in seven PETE-bottled water brands, representing major producing firms in Jeddah city. On the same day samples brought from local superstores, each sample underwent 4-replicate analysis (as time-zero Sb level). Soon after analysis, bottles of each brand were tightly closed, divided into three subsets, stored for 2 months (23°C, 5°C, 50°C, respectively), then re-analyzed. ICP-OES was used for analysis. Sb ranged from 0.100 (time-zero) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The increase in levels of Antimony could be attributed to effects of pH, temperature and UV radiation (Fig. 2) from the sun, supported by experiments from (Al-Khatim et al, 2019;Chapa-Martínez et al, 2016;Dogan and Cebi, 2019;Zmit and Belhaneche-Bensemra, 2019) which identified the significance of pH, temperature and days of exposure in the amount of Antimony leached into bottled water. The high level of the Antimony values can also be attributed to the type of plastics used by the different brands as identified by (Koyuncu and Alwazeer, 2019) who suspected reason for high Antimony levels in milk contained in PET bottles results from type and production processes employed in making containers.…”
Section: Antimonymentioning
confidence: 72%
See 1 more Smart Citation
“…The increase in levels of Antimony could be attributed to effects of pH, temperature and UV radiation (Fig. 2) from the sun, supported by experiments from (Al-Khatim et al, 2019;Chapa-Martínez et al, 2016;Dogan and Cebi, 2019;Zmit and Belhaneche-Bensemra, 2019) which identified the significance of pH, temperature and days of exposure in the amount of Antimony leached into bottled water. The high level of the Antimony values can also be attributed to the type of plastics used by the different brands as identified by (Koyuncu and Alwazeer, 2019) who suspected reason for high Antimony levels in milk contained in PET bottles results from type and production processes employed in making containers.…”
Section: Antimonymentioning
confidence: 72%
“…Leaching of chemicals from PET bottles have been investigated by (Abboudi et al, 2018;Al-Khatim et al, 2019;Zmit and Belhaneche-Bensemra, 2019). This study found that for each of the parameters the following conclusions apply:…”
Section: Resultsmentioning
confidence: 97%
“…The increase in the levels of antimony could be attributed to the effects of pH, temperature, and UV radiation (Fig. 2) from the Sun, supported by researchers who identified the significance of pH, temperature, and days of exposure in the amount of Antimony leached into bottled water (Al-Khatim et al, 2019;Chapa-Martínez et al, 2016;Dogan and Cebi, 2019;Zmit and Belhaneche-Bensemra, 2019). The high level of the antimony values can also be attributed to the type of plastics used by the different brands as identified by Koyuncu and Alwazeer (2019), who suspected that the reason for the high antimony levels in milk contained in PET bottles results from the type and production processes employed in making containers.…”
Section: Antimonymentioning
confidence: 76%
“…Leaching of chemicals from PET bottles has been investigated in the literature (Abboudi et al, 2018;Al-Khatim et al, 2019;Zmit and Belhaneche-Bensemra, 2019). This study found that, for each of the parameters, the following conclusions apply:…”
Section: Resultsmentioning
confidence: 99%